2012
DOI: 10.1163/1568539x-00003008
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of egg-covering in the Kentish plover Charadrius alexandrinus

Abstract: Many bird species take recesses during incubation, and while the nests are unattended, the eggs may both be vulnerable to predation and reach suboptimal temperatures for embryo development. Perhaps to avoid these negative possibilities, some birds cover their eggs with materials when they depart from nests. We examined experimentally, using the ground-nesting Kentish plover as model species, whether egg-covering allows egg temperatures to remain within optimal limits for embryogenesis in unattended nests, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 45 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The importance of the materials in improving camouflage may be especially significant when the match between the nesting habitats and the eggs is poor. In such cases, the birds may improve egg camouflage with the materials that they add to nests (Amat et al, 2012; Troscianko et al, 2016a). This in turn shows that some birds are selective in their choice of nesting materials (Kull, 1977; Solís and de Lope, 1995; Gómez et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the materials in improving camouflage may be especially significant when the match between the nesting habitats and the eggs is poor. In such cases, the birds may improve egg camouflage with the materials that they add to nests (Amat et al, 2012; Troscianko et al, 2016a). This in turn shows that some birds are selective in their choice of nesting materials (Kull, 1977; Solís and de Lope, 1995; Gómez et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Our results instead suggest that a combination of individual habitat preferences or site fidelity may predict the structure of breeding territories. Habitat preferences may be linked to local variation in ambient temperatures, predator densities, as well as the availability of different nest substrates or nest cover, which can have strong implications for the success of nesting attempts in Kentish plover via heat stress to eggs and predation risk 47 , 68 71 . In addition, we found no evidence that the number of breeding pairs within 100 m of a focal bird’s nest, influenced their nesting success.…”
Section: Discussionmentioning
confidence: 99%
“…Such behaviours include nest distraction displays (Gochfeld, 1984; Gómez-Serrano & López-López, 2017), or even varying flushing distances by incubating adults depending on the degree of nest camouflage (Wilson-Aggarwal et al ., 2016; Amat et al ., 2017). Moreover, shorebirds may intentionally modify the visual appearance of nest sites by adding materials that render the eggs/nests harder to find visually (Solís & de Lope, 1995; Gómez et al ., 2018), and may even use these materials to cover the eggs during parental absences from the nest, resulting in even better camouflage (Summers & Hockey, 1981; Amat et al ., 2012; Troscianko et al ., 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…flage (Summers & Hockey, 1981;Amat et al, 2012;Troscianko et al, 2016a). Mayani-Parás et al (2015) reported another possible behaviour used by ground-nesting birds to improve egg camouflage.…”
Section: Introductionmentioning
confidence: 99%